2017
DOI: 10.2337/db17-0867
|View full text |Cite
|
Sign up to set email alerts
|

Insights From Molecular Characterization of Adult Patients of Families With Multigenerational Diabetes

Abstract: Multigenerational diabetes of adulthood is a mostly overlooked entity, simplistically lumped into the large pool of type 2 diabetes. The general aim of our research in the past few years is to unravel the genetic causes of this form of diabetes. Identifying among families with multigenerational diabetes those who carry mutations in known monogenic diabetes genes is the first step to then allow us to concentrate on remaining pedigrees in which to unravel new diabetes genes. Targeted next-generation sequencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…It was reported that 3% of hyperglycemic adults diagnosed as having type 2 diabetes (T2D) are affected by a multigenerational disease (Ludovico et al, 2015;Pezzilli et al, 2018). Here we first show the evidence from patients with multigenerational diabetes and two mouse models supporting the pivotal role of both human KCNH6 (Kv11.3) and mouse Kcnh6 in the regulation of insulin secretion.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…It was reported that 3% of hyperglycemic adults diagnosed as having type 2 diabetes (T2D) are affected by a multigenerational disease (Ludovico et al, 2015;Pezzilli et al, 2018). Here we first show the evidence from patients with multigenerational diabetes and two mouse models supporting the pivotal role of both human KCNH6 (Kv11.3) and mouse Kcnh6 in the regulation of insulin secretion.…”
Section: Introductionmentioning
confidence: 68%
“…We know that MODY prevalence is low, and we should be cautious to interpret KCNH6 p.P235L Mut as the cause of a new MODY Mut. Of hyperglycemic adults diagnosed as having T2D, 3% are affected by multigenerational monogenic diabetes (Ludovico et al, 2015;Pezzilli et al, 2018). Usually, these patients present with the typical of metabolic abnormalities observed in T2D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs when suspected MODY cases represent other types of diabetes (e.g., type 1 or 2) that can also occur in young individuals and/or coexist with other affected family members, thus mimicking the phenotype of MODY, but with no monogenic cause. As diabetes is a relatively common disease, the existence of several affected family members does not necessarily imply an inherited cause of diabetes [31]. Furthermore, the fact that mutation-negative patients in our study were diagnosed at a later age suggests that these are less likely to be associated with a genetic cause.…”
Section: Discussionmentioning
confidence: 70%